Exploring the effects of communication structures on intergroup behaviour - Tay, Clarice (Nanyang Technological University, 2023)
This study aims to investigate whether communication structures induce constructive conflict and affect intergroup behaviours (competitive and cooperative) and overall welfare. We conducted a laboratory experiment consisting of two stages — inducement of group identities and an adapted Tullock rent-seeking contest. Our results show that communication between identity groups increases cooperative behaviour whereas communication within groups increases competitive behaviour. Overall, communication between groups led to higher welfare. Compared to subjects who communicated within groups, those who communicated between groups were as cooperative but more competitive when they played with their outgroup relative to their ingroup. Constructive conflict was positively related to welfare and negatively related to competitive behaviour, but not related to cooperative behaviour. This study provides support for the idea that communication across identity groups is crucial for developing mutual trust and understanding to develop to sustain social capital.